The Influence of Enterprise Risk Management on Corporate Performance with The moderating Effect of Intellectual Capital - Vega Ariya Samudera; Husaini Husaini (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
The purpose of this study is to examine the effect of the application of ERM on the corporate financial performance and corporate market performance. Furthermore, this study also examines the influence of intellectual capital in moderating the relationship of ERM to corporate financial performance and corporate market performance. The sample in this study is banking companies listed on the Indonesia Stock Exchange with the period 2018-2022. The results of this study show that ROI-based ERM has an influence on the corporate financial performance and the corporate market performance. ROA-based ERM has an influence on the corporate financial performance, but it has no influence on market performance. Intellectual capital has a moderator effect on the relationship between ROI-based ERM on a corporate financial performance and a corporate market performance. Intellectual capital has a moderator effect on the relationship between ROA-based ERM and a corporate financial performance, but it does not have a moderator effect on the relationship between ROA-based ERM on a corporate market performance.